The Combined Effect of Lower Extremity Function and Cognitive Performance on Perceived Walking Ability Among Older People: A 2-Year Follow-up Study. (8th May 2018) - Siltanen, Sini; Portegijs, Erja; Saajanaho, Milla; Poranen-Clark, Taina; Viljanen, Anne; Rantakokko, Merja; Rantanen, Taina
Abstract: Background: We studied the combined effects of cognitive performance and lower extremity function on self-reported walking modifications and walking difficulty and on self-reported walking difficulty incidence over a 2-year follow-up. Methods: A total of 848 community-dwelling older people aged 75–90 years participated at baseline, 816 at the 1-year follow-up, and 761 at the 2-year follow-up. Baseline lower extremity function was measured with the Short Physical Performance Battery (<10 vs. ≥10) and cognitive performance with the Mini–Mental State Examination (<24 vs. ≥24). Difficulty in walking 2 km was self-reported and categorized into no difficulties, no difficulties but walking modifications, and prevalent difficulties. Data were analyzed with multinomial and Cox regressions and a mediation analysis. Results: At baseline, 33% reported no walking difficulties, 25% walking modifications, and 42% walking difficulty. Poorer lower extremity function and lower cognition increased the odds for walking difficulty. For those with both, the odds were almost eightfold higher for walking difficulty and threefold higher for walking modifications compared with having neither. Poorer lower extremity function mediated the association between low cognition and poorer perceived walking ability. Of those with no walking difficulty at baseline, 31% developed walking difficulty during the follow-up, the risk being almost twofold higher among those with poorer lower extremity function at baseline (hazard ratio = 1.82, 95% confidence interval = 1.28–2.59). Conclusion: Older people with poorer lower extremity function and cognitive performance are likely to have walking difficulties, rendering them especially vulnerable to further disability. Cognitive performance should be considered in interventions aimed at preventing mobility disability.